Cover Feature: "Click" Silica‐Supported Sulfonic Acid Catalysts with Variable Acid Strength and Surface Polarity (Chem. Eur. J. 27/2019). Issue 27 (8th April 2019) - Kasinathan, Palraj; Lang, Charlotte; Radhakrishnan, Sambhu; Schnee, Josefine; D'Haese, Cécile; Breynaert, Eric; Martens, Johan A.; Gaigneaux, Eric M.; Jonas, Alain M.; Fernandes, Antony E.
Abstract : How do you like your acid catalyst? A robust and modular method is presented for the preparation of silica‐supported sulfonic acid catalysts. The strategy makes it possible to fine tune both their acid strength and surface polarity, taking advantage of the copper‐catalyzed azide‐alkyne cycloaddition (CuAAC) and further modification of the formed triazole link. The artwork displays an assembly line that reacts the azide‐functionalized mesoporous silica particles with different alkynes and electrophiles to provide a family of bespoke solid acid catalysts. More information can be found in the Full Paper by A. E. Fernandes et al. on page 6753 .